Analysing welfare reform in a microsimulation-AGE model: the value of disaggregation - Melanie Arntz; Stefan Boeters; Nicole Gürtzgen; Stefanie Schubert (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
We present a combined, consistent microsimulation-AGE model that uses the labour market model PACE-L, data from the German Socio-Economic Panel and a discrete choice labour supply estimation. The model is used to analyse a reform that cuts the social assistance minimum income and lowers the transfer withdrawal rate in order to encourage labour force participation at the lower end of the wage distribution. We compare a disaggregated and an aggregated version of the model as well as a partial and a general equilibrium variant. It turns out that both disaggregation and general equilibrium feedback tend to mitigate the labour supply response to the reform proposal. While some labour supply indicators react quite sensitively to the level of aggregation, most macroeconomic variables are considerably more robust.
Keywords: D58; J51; J22; 330; applied general equilibrium; discrete working time choice; labour market; wage bargaining; labour market reform; logit model; microsimulation